Kontruksi Sosial Network Analysis Untuk Menilai Kepopuleran Brand Sepatu di Twitter - Setyo Hendro Prayoga; Widiyanto Tri Handoko (Universitas Budi Darma, 2023)
Shoes are one of the most popular products to buy. Therefore, many well-known shoe brands such as Adidas, Converse, New Balance, Nike, Reebok and Skechers are competing to create the latest shoe models. Many shoe brand users share their experiences on the Twitter platform. The aim of this research is to assess the level of popularity of the Adidas, Converse, New Balance, Nike, Reebok, Skechers shoe brands on the Twitter platform. This research will analyze the social network patterns of Twitter users in the period January - March 2023 which discusses the shoe brands Adidas, Converse, New Balance, Nike, Reebok, Skechers and will be analyzed using Social Network Analysis (SNA). SNA is a method that can be used to analyze interactions between individuals that occur on the Twitter platform by looking at network properties. This research will also use the Weighted Aggregated Sum Product Assessment (WASPAS) method which is used to support decision making about which shoe brands are the most popular in the period January – March 2023. The results of this research show that New Balance obtained rank 1 with a value of 0.985172467, Adidas was ranked 2nd with a value of 0.946380309, Nike was ranked 3rd with a value of 0.851347847, Reebok was ranked 4th with a value of 0.83674501, Converse was ranked 5th with a value of 0.831588591, and Skechers was ranked 6th with a value of 0.759538181.